Lateral luxation of the elbow and its treatment in a kitten - Polat, E. (Hellenic Veterinary Medical Soc, 2025)
Elbow luxations are an uncommon orthopedic issue in kittens. The main objective of treating such luxations is to minimize restrictions on the range of motion in the cubiti joint. While various techniques are employed for this purpose, diverse treatment options are still necessary. This report focuses on the lateral luxation of the elbow and its treatment in a three-month-old cat, emphasizing the importance of an operative technique that does not hinder normal elbow joint movements and serves as an alternative to standard methods. During the operation, the radius bone was secured to the ulna bone using an orthopedic pin, and the elbow luxation was stabilized with a cerclage wire. The patient began using its foot on the third day of the postoperative period and underwent a four-month follow-up. Subsequent interviews with the patient's owner revealed the patient's favorable condition, with the ability to use its foot comfortably.
Keywords: Cat; Dislocation; Elbow